TANGGUNG JAWAB JABATAN DAN TANGGUNG JAWAB PRIBADI DALAM PENYELENGGARAAN PEMERINTAHAN DI INDONESIA - Sufriadi, Sufriadi (Jurnal Yuridis, 2014)
Giving great authority to the organs of government to be involved in most aspects of public life is the philosophical consequences of the welfare state understand which adopted by Indonesia constitution adopted. To carrying out the task for the general welfare, the authority which used the organs of government, based on the provisions of the legislation (principle of legality). However, not infrequently, the task was carried out on the basis of free authority(discretionary). In practical terms, this condition is highly vulnerable to violations of the rights of citizens, although within the framework of the concept of state substantive law, the use of discretion by the Government is no longer debatable. In this context, an understanding of government liability needs to be done. In the concept of public law, legal liability is closely related to the use of authority, which gave rise to the principle that 'no authority without responsibility'. There comes a time that the organs of government officials are held liable as, and sometimes as a person representing himself.